A Comparative Study of Justice from the Viewpoint of Shahid Motahhari and Aristotle - Mousavimoghadam, Seyed Rahmatollah (International Journal of Psychosocial Rehabilitation, 2020)
Introduction:The concept of justice is one of the fundamental principles of development, human evolution and civilization. The purpose of this research is the comparative study of justice from the perspective of Shahid Motahhari and Aristotle. Method:This research method was used in this study Library and data collection was done through taking note from the reference books, articles and valid manuscripts. Discussion:The results showed that Aristotle, as a great Western philosopher and Shahid Motahhari as an Islamic thinker and philosopher, both regard justice as one of the central virtues; Aristotle defines justice, the final good of humans, as the soul’s activity in accordance with virtue and regards it as "average" in opposed to going to extremes. In Aristotle’s view, justice is a complete virtue. In Motahhari’s view, justice has a spiritual and ideal face and is not subject to the taste or desire of human beings. In this approach, justice is defined and achieved in the strict conformity with the objective "right"; it is expressed as observance of an individual or object’s entitlement. In the religious and Islamic view, it cannot be reduced to the satisfaction, desirability, or social contract which constitutes the epistemological basis of liberal justice". Conclusion:Understanding the concept of justice by Aristotle as the "average" is rather conceptual and, in practice, its application is complicated and sometimes impossible; in Motahhari’s view, justice is objective and a criterion that must become practically a norm. His view of justice in terms of objectivity and practicability is more useful.